Integrated Procurement System As A Catalyst For Bumn Procurement Digitalization: Resistance And Opportunities - Rachma Wahyu Illahi; Lilik Purwanti; Virginia Nur Rahmanti (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study aims to explore user resistance to the implementation of the Integrated Procurement System (IPS) as part of the digitalization of goods and services procurement within state-owned enterprises (BUMN) in the plantation sector, specifically in PT Perkebunan Nusantara (PTPN) Group. The primary focus is to identify the underlying factors of resistance, assess its impact on system effectiveness, and formulate appropriate change management strategies. Methodology/approach: This research employs a transcendental phenomenological methodology to uncover the subjective meanings behind users’ experiences with the IPS. Data were collected through in-depth interviews and observations involving procurement staff, finance, legal, regional management, and vendors. The Technology Acceptance Model (TAM) serves as the analytical framework to understand user perceptions regarding perceived usefulness, perceived ease of use, perceived trust, and perceived security in the context of digital system adoption. Findings: The study reveals five main causes of resistance: lack of understanding, aversion to change, fear of audits, leadership gaps, and conflicts of interest. These factors led to delayed financial processes and weakened internal control. However, the study also found opportunities such as improved transparency, digital leadership, and potential integration of AI in procurement workflows. Practical implications: The study offers strategic recommendations, including awareness-based training, the use of artificial intelligence (AI), the strengthening of transformational leadership roles, and the harmonization of digital regulations to enhance the effectiveness of IPS implementation in BUMN environments. Originality/value:This study provides a novel contribution by deeply understanding users’ subjective experiences during IPS implementation in state-owned enterprises. Through a transcendental phenomenological approach, the research uncovers the meaning embedded in these experiences to identify resistance factors, analyze their impact on system effectiveness, and develop context-specific change management strategies aligned with the organization’s characteristics. The use of the Technology Acceptance Model (TAM) as an analytical tool structures the findings and offers a holistic perspective on user resistance, encompassing technical, psychological, and social dimensions.